Shakespeare and the Formation of the Modern Economy - Waswo, Richard (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
Describing money and words as homologous systems that function to constitute, transmit, and alter values permits this essay to explore the formative period of the modern economy, when sixteenth-century writers were struggling to conceptualize it, and Shakespeare was dramatizing its basic principles.